Pengaruh Kualitas Produk dan Citra Merek terhadap Minat Beli Laptop Acer pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Pembangunan Nasional “Veteran” Jawa Timur - Hermawan Kristanto; Hery Pudjoprastyono (Jurnal Ekonomi, 2021)
In the development of the era of laptops, many are presented with different specifications and advantages. Manufacturers compete with each other to win the hearts of consumers by presenting their respective superior products. Thus the Acer company needs to improve the quality of its products and brand image in order to be able to attract consumer buying interest. This study aims to determine the effect of product quality, brand image on buying interest in Acer laptops. The population in this study were students of the Faculty of Economics and Business, UPN "Veteran" East Java. The sampling method uses probability sampling, namely the Proportionate Stratified Random Sampling technique. The sample taken amounted to 97 respondents. The data used are primary data, namely questionnaire data from answers to respondents and secondary data, namely supporting data obtained from the top brand index (TBI). While the analysis used is Partial Least Square (PLS). Based on the results of the study, it was stated that product quality and brand image contributed to buying interest in Acer laptop products.